ASYMMETRIC SYNTHESES OF ETHYL (S)-(+)-2-METHYLHEPT-4-YNOATE USING BOTH ENANTIOMERS OF THE CHIRAL IRON AUXILIARY [(ETA-5-C5H5)FE(CO)(PPH3)] - Bodwell, G; Davies, S (1991)
The asymmetric syntheses of ethyl (S)-(+)-2-methylhept-4-ynoate via double alkylations of the homochiral acetate equivalents (R)- and (S)-[(η5-C5H5)Fe(CO)(PPh3)COCH3] are described. © 1991.